The Relationship Between Family Firm Heterogeneity and Tax Avoidance - Ary Zalaza Ceradhina Rahmadhani; Heru Tjaraka (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2022)
Research purposes: This study aims to obtain empirical evidence about the relationship of the role of the founder in family firm heterogeneity and tax avoidance, with the executive character as a moderating variable.Methods: The population in this study is obtained from listed family companies on the Indonesia Stock Exchange from 2016 – 2019. The hypotheses in this study were tested with OLS (ordinary least square). This study used purposive sampling as the sampling method, in which it produced 134 companies as the research sample.Findings: The findings of this study show that the substantial ownership of founders has a significant positive effect on tax avoidance. Furthermore, founders of family firms who occupy positions as a board of commissioners significantly negatively affect tax avoidance. This study also indicates that the executive characters can moderate the influence of the founder’s role in family firm heterogeneity on tax avoidanceNovelty: This research was using the family firm as a sample of research from Indonesia Stock Exchange so it can enrich the literature about family firm in Indonesia. This research also used the role of the founder of the family firms as an independent variable.